Short uncemented stems allow greater femoral flexibility and may reduce peri-prosthetic fracture risk: a dry bone and cadaveric study - Jones,C; Aqil,A; Clarke,S; Cobb,JP (Journal of Orthopaedics and Traumatology, 2015)
BackgroundShort femoral stems for uncemented total hip arthroplasty have been introduced as a safe alternative to traditional longer stem designs. However, there has been little biomechanical examination of the effects of stem length on complications of surgery. This study aims to examine the effect of femoral stem length on torsional resistance to peri-prosthetic fracture.Materials and methodsWe tested 16 synthetic and two paired cadaveric femora. Specimens were implanted and then rapidly rotated until fracture to simulate internal rotation on a planted foot, as might occur during stumbling. 3D planning software and custom-printed 3D cutting guides were used to enhance the accuracy and consistency of our stem insertion technique.ResultsSynthetic femora implanted with short stems fractured at a significantly higher torque (27.1 vs. 24.2 Nm, p = 0.03) and angle (30.3° vs. 22.3°, p = 0.002) than those implanted with long stems. Fracture patterns of the two groups were different, but showed remarkable consistency within each group. These characteristic fracture patterns were closely replicated in the pair of cadaveric femora.ConclusionsThis new short-stemmed press-fit femoral component allows more femoral flexibility and confers a higher resistance to peri-prosthetic fracture from torsional forces than long stems.